The Effects of Work Stress and Work Motivation on Employee Performance - Sandiyudha Wirabuana Putra; Maat Pono; Wahda (Ilomata International Journal of Management, 2023)
High levels of work stress (WS) can significantly lower work motivation (WM) as the energy is prone to deplete, causing burnout, and undermining employees’ belief to succeed in their career. On the other hand, low motivation level makes them more susceptible to experiencing WS and less resilient in coping with stressful situations. Thus, what is the connection between WS and WM on employee performance (EPf)? In fact, there are still few researches discussing the issue, particularly in telecommunications companies and this became the background for this study. To conduct the research, qualitative and quantitative data are used. The population comprised all employees of PT Hutchison 3 Indonesia (H3I) Makassar Branch who also become a sample or census sampling. For the data collection, a survey method is implemented with multiple linear regression as its technique of analysis. The results showed that the variables of WS and WM had a positive and significant impact on EPf. All research hypotheses are declared accepted, which indicates that an increase in the variables of WS and WM will improve EPf. The findings contribute to the development of theory and practice in the fields of performance and human resources management.